2012
DOI: 10.3844/ajidsp.2012.13.18
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Quality of Life of Women with HIV/AIDS

Abstract: Problem statement:HIV infection is a multisystem disorder which causes chronic infections that lead to profound immune-suppression. Women have always been a vulnerable section of the society. They are doubly vulnerable due to the HIV and malnutrition vicious cycle, which may affect their Quality Of Life (QOL). There are different literature reviews which suggest undernutrition, wasting due to HIV but it is important to know whether this under-nutrition affects their Quality Of Life (QOL) of these vulnerable wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
3
5
1
Order By: Relevance
“…This finding was supported by the study from Nepal [17] and India [36]; that showed most of health related quality of life domains of PLWHA were significantly decreased as body mass index lowered. A study from South Africa also found that physical and independence health were affected by daily energy intake [10].…”
Section: Discussionsupporting
confidence: 62%
“…This finding was supported by the study from Nepal [17] and India [36]; that showed most of health related quality of life domains of PLWHA were significantly decreased as body mass index lowered. A study from South Africa also found that physical and independence health were affected by daily energy intake [10].…”
Section: Discussionsupporting
confidence: 62%
“…Improvement in nutritional status was in terms of improvement in SGA or MUST score and weight gained or lost. However, no consensus has been reached at the moment on the actual influence that nutrition plays in quality of life in PLWHA [7]. The current study, thus aimed at further investigating the relationship between nutritional assessment parameters and quality of life in a cohort of HIV-seropositive patients and identifying nutritional variables that best predicts weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life (QOL) also plays an important aspect in the overall care of PLWHA. World Health Organization (WHO) has defined QOL as an individuals' perception of their position in life in the context of their culture and value system in which they "live and in relation to their goals, standards, expectations and concerns" [5]- [7]. The 26-item WHOQOL-Bref, is a validated tool that measures quality of life in PLWHA in four different domains: 1) physical domain (assesses the individual's perception of impact of disease on the activities of daily living, dependence on medication, lack of energy and initiative, restricted mobility and capacity to work); 2) psychological domain (assesses the individual's satisfaction with thoughts about body image and appearance, negative feelings, positive feelings, self-esteem and personal beliefs); 3) social relations (assesses personal relationships, social support and sexual activity); 4) environmental domain (assesses satisfaction with financial resources, work environment, accessibility to health and social care, freedom, security, participation and opportunities for leisure activities) [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations